2016
DOI: 10.1002/jbm.a.35634
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the donor cell contribution in rhBMP‐2 mediated bone formation with chitosan thermogels using fluorescent protein reporter mice

Abstract: Our current understanding regarding the contribution of donor cells in growth factor and cell based tissue regeneration strategies is limited. The present study attempts to utilize fluorescent protein reporter mice [Col3.6Topaz (enhanced yellow fluorescent protein, EYFP) as host and Col3.6Cyan (enhanced cyan fluorescent protein, ECFP) as donor] to determine donor cell contribution in bone regeneration using a bilateral calvarial defect model. Thermogelling chitosan hydrogels (Chi-AHP) were used as bone marrow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(169 reference statements)
0
5
0
Order By: Relevance
“…Also, BGP and ALP genes play critical roles in osteoblast differentiation . Well‐Known as markers of bone formation and disruption, strong ALP and TRAP activity suggests active mineralizing and remodeling as well as mature lamellar bone matrix . According to a previous study, ALP activity was increased with the combination of BMP‐2 and dexamethasone synergistically through the activation of signal transducer and activator of transcription 3 (STAT3) signaling pathway in C3H10T1/2 cells .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, BGP and ALP genes play critical roles in osteoblast differentiation . Well‐Known as markers of bone formation and disruption, strong ALP and TRAP activity suggests active mineralizing and remodeling as well as mature lamellar bone matrix . According to a previous study, ALP activity was increased with the combination of BMP‐2 and dexamethasone synergistically through the activation of signal transducer and activator of transcription 3 (STAT3) signaling pathway in C3H10T1/2 cells .…”
Section: Discussionmentioning
confidence: 98%
“…39 Well-Known as markers of bone formation and disruption, strong ALP and TRAP activity suggests active mineralizing and remodeling as well as mature lamellar bone matrix. 40,41 According to a previous study, ALP activity was increased with the combination of BMP-2 and dexamethasone synergistically through the activation of signal transducer and activator of transcription 3 (STAT3) signaling pathway in C3H10T1/2 cells. 42 It has been reported that with elevated ALP activity and enhanced mineralization, appropriate plasma irradiation promotes differentiation of osteoblasts, which might be a potential target for bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Gohil, S. V. et al [ 11 ] investigated the viability of utilizing calcium-hydroxyapatite (Chi-AHP) and Chi-AHP with rhBMP-2 for promoting bone regeneration. After four weeks, the Chi-AHP-implanted defect sites exhibited restricted cellular infiltration but no mineralized tissue formation or ALP/TRAP activity.…”
Section: Resultsmentioning
confidence: 99%
“…Full-text articles excluded, with reasons (n = 17) No use of MSCs (5). No BMP therapy (11). Reviews (1).…”
Section: Mice Modelsmentioning
confidence: 99%
See 1 more Smart Citation